COMPUTER-TOMOGRAPHIC MESIODISTAL DIMENSIONS OF TEETH IN BOYS AND GIRLS WITH PHYSIOLOGICAL BITE DEPENDING ON FACE TYPES - Pozur, T.P.; Shinkaruk-Dykovytska, М.М.; Gavryluk, A.O.; Gnenna, V.O.; Shcherba, I.K.; Yasko, V.V.; Yakubovska, O.M. (World of Medicine and Biology, 2018)
The purpose of the work is to establish the boundaries of the percentile scope and the peculiarities of the computer-tomographic mesiodistal dimensions of the upper and lower jaw teeth in boys and girls with physiological bite, depending on the type of person. Primary computer-tomographic dimensions of the width of the crowns of the teeth and the width of the teeth at the level of the anatomical neck in the mesiodistal direction with normal occlusion close to the orthognathic bite and the cephalometric parameters of 44 boys and 50 girls of the Podillia region of Ukraine were obtained from the data bank of the research center of the National Pirogov Memorial Medical University, Vinnytsya. Face type was determined using the Garson morphological index. The statistical processing of the obtained results was carried out using the statistical software package "Statistica 6.0" using non-parametric estimation methods. In boys and girls with normal occlusion close to orthognathic bite with different types of face the boundaries of the percentile width of the crowns and teeth widths at the level of the anatomical neck in the mesiodistal direction are determined. It has been established that in young men with wide faces, practically all dimensions of the width of the crowns of the teeth in the mesiodistal direction (with the exception of the lower second premolars) are significantly higher or tend to be higher than that of girls with a wide face; as well as in broad-faced boys, most of the size of the teeth width at the anatomical neck level in the mesiodistal direction (with the exception of the lower central and lateral incisors) is significantly higher than that of girls with a broad face. When comparing discrepancies between the computer tomographic size of the teeth crowns and teeth widths at the anatomical neck level in the mesiodistal direction between girls with a broad and very wide face, only a significantly higher value of the width of the upper central incisors at the level of the anatomical neck in girls with very wide faces was established.
Keywords: boys; girls; face type; computer tomography; mesiodistal dimensions of teeth; physiological bite; sexual differences